Management of extravasation of drugs applied in cancer therapy - Karczmarek-Borowska, Bożena; Matczuk, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2004)
During chemotherapy besides the systemic side effects also local side effects may occur such as those observed after drug extravasation. Topical reaction may occur during or after completion of therapy. The consequences of extravasation vary from mild rubor and pain to necrosis and deep injury of adjacent tissues and venous vessel patency disorders. Cytostatic drug extravasation is described as an unintended leak or transudation of administered drug to perivascular or subcutaneous space. Factors that influence the degree of adjacent tissue damage include: the status of venous vessels, cannulation technique, drug concentration, the size of extravasation and its localization. To avoid the topical reaction careful observation of injection site during drug administration is recommended. When extravasation occurs some locally acting drugs may be administered. There are specific agents that are recommended in such cases for some cytostatics such as cisplatin, dactinomycin, doxorubicin, epirubicin, idarubicin, mitomycin, mitoxantrone, paclitaxel, docetaxel and vinca alkaloids. Locally acting agents utilized to date include sodium thiosulfate, hyaluronidase, dimethylsulfoxide and steroids. There are no specific antidotes for other cytostatic drugs. In the case of topical reaction after they were administered, to avoid severe complications concerning the place of extravasation, subcutaneous injection of isotonic salt solution and/or hyaluronidase, or a cold compress may be applied. When there is deep and long-lasting ulceration, surgical intervention is recommended. The aim of the study is the analysis of factors involved in extravasation, methods of prevention and management of cases of extravasation.